DISFLUENCIES IN STAND-UP COMEDY: A PSYCHOLINGUISTIC ANALYSIS ON DREW LYNCH'S STUTTERING - Widya Nindi Hardianti; Rohmani Nur Indah (Leksema: Jurnal Bahasa dan Sastra, 2020)
Difficulties of producing speech sound in stutterers are indicated by the repetition, pause, prolongation, revision, and filled pause on the speaking. However, such difficulties do not hinder the communication as shown in the speech of a stand-up comedian named Drew Lynch. This study aims at exploring the types of fluency disorder identified in Lynch’s utterances on stage. This study uses the descriptive qualitative method employed through the process of observing, transcribing, describing, and analyzing his utterances in American Got Talent videos. The result shows Lynch produces all kinds of disfluency covering filled pause, phrase repetition, revision, multisyllabic whole-word repetition, monosyllabic whole-word repetition, repetition of individual sound or syllable, prolongation of sound, and block. The monosyllabic whole-word repetition is more dominant. The combination happens between revision with monosyllabic whole-word repetition, prolongation, or multisyllabic whole-word repetition. These findings confirm that in the context of stand-up comedy, the disfluencies in stuttering do not hamper the transfer of meaning.